DIFFERENCE IN MAIN CATCH, BY-CATCH, AND DISCARD RESULTS ON THE WAVE THAT IS OPERATED DAY AND NIGHT IN SIALANG PASUNG VILLAGE, MERANTI ISLAND REGENCY - Yuliawati, Yuliawati; Brown, Arthur; Rengi, Pareng (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThis research was conducted on 13-19July 2018, located in Sialang Pasung Village, Meranti Islands Regency. The purpose of this study is to find out the main catch, by-catch and discard, and to find out the difference between day and night catches. The method used in this study is the survey method, namely, making direct observations in the field of the catch on the wave fishing gear, then each fish catch is identified, counting the number of fish and weighing the weight of fish. the object used is the catch on the wave fishing gear. The research results are described in graphical form. The results showed the highest value of the main catch during the day, by-catch in the afternoon and discard at night. Keyword: Sialang Pasung village Meranti island, catch, catching tool